2022
DOI: 10.1021/acsomega.2c02948
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on the Effect of NO2 on n-Butanol/Biodiesel Dual-Fuel Combustion in a Compression Ignition Engine

Abstract: Nitrogen dioxide (NO 2 ) is an active species of exhaust gas recirculation gas, and it has a significant impact on the autoignition and combustion processes of fuels. This study presented a comprehensive investigation of the effect of NO 2 on the combustion characteristics of the n -butanol/biodiesel dual fuel. Experiments were conducted on a single-cylinder engine with 0, 100, 200, and 400 v/v ppm NO 2 addition at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Adding 40% of 1-butanol to the biodiesel tends to improve the acceleration of OH radicals at a much faster rate to achieve fine BTE, lower the BSFC, and lower NO X emissions compared to diesel. 35 This study investigates the diesel engine performance, combustion, and emission parameters of the various test blends RP100, D90RP7B3, D80RP14B6, and D70RP21B9. Most of the literature that used 1-butanol with different biodiesel reported that it gives predetermined performance and minor emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding 40% of 1-butanol to the biodiesel tends to improve the acceleration of OH radicals at a much faster rate to achieve fine BTE, lower the BSFC, and lower NO X emissions compared to diesel. 35 This study investigates the diesel engine performance, combustion, and emission parameters of the various test blends RP100, D90RP7B3, D80RP14B6, and D70RP21B9. Most of the literature that used 1-butanol with different biodiesel reported that it gives predetermined performance and minor emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The NO X emissions were reduced by 4%. Adding 40% of 1-butanol to the biodiesel tends to improve the acceleration of OH radicals at a much faster rate to achieve fine BTE, lower the BSFC, and lower NO X emissions compared to diesel …”
Section: Introductionmentioning
confidence: 99%